The Relationship Between Sitting Posture When Using Digital Devices and the Risk of Low Back Pain in Final Year Students - Novita Sari; Lili Eky Nursiah N; Eva Flourentina Kusumawardani; Jun Musnadi Is; Dian Fera (Universitas Ahmad Dahlan, 2025)
Background: Low Back Pain (LBP) refers to discomfort in the lower back and is recognized as the leading cause of global disability, with 619 million cases reported in 2020. This number is expected to rise as students become increasingly dependent on digital devices due to technological advancements. Non-ergonomic sitting postures while using laptops or smartphones may increase spinal pressure and contribute to functional impairments. This study aims to examine the relationship between sitting posture when using digital devices and the risk of LBP among final-year Public Health students. Method: A cross-sectional analytical study was conducted with 117 respondents selected through simple random sampling from a population of 168 students. Sitting posture was assessed using the Rapid Entire Body Assessment (REBA) method, and the risk of LBP was measured using the Oswestry Disability Index (ODI) questionnaire. Results: The results showed that most students adopted non-ergonomic sitting postures (60.7%), with the highest proportion experiencing moderate disability (41.9%). Statistical analysis revealed a significant association between sitting posture and LBP risk (P = 0.00). Conclusion: There is a significant relationship between sitting posture and the risk of LBP among students. Poor posture increases the likelihood of functional limitations due to back pain. It is recommended that students adopt ergonomic sitting habits and perform regular stretching to reduce LBP risk. These findings may serve as a reference for developing targeted health promotion and prevention strategies within the university setting.